Conditional Decisions as Instrument Guarding the Supremacy of the Constitution (Analysis of conditional decisions of Indonesian Constitutional Court in 2003 - 2017) - Safa'at, Muchamad Ali; Eko Widiarto, Aan (Brawijaya Law Journal, 2021)
The function of the Indonesian Constitutional Court as the guardian of the constitution is mainly conducted through the judicial review authority. From 2003 to April 2021, the Constitutional Court has received and decided 1392 petitions over judicial review. In its dictums, the Constitutional Court often declares conditionally constitutional or conditionally unconstitutional (conditional decision). The conditional decision is a decision of the Court that declares the reviewed norm conditionally constitutional or unconstitutional. The norm is constitutional if interpreted according to the Court interpretation, or the norm is unconstitutional if interpreted in specific ways. This research investigates the criteria of judicial review decisions that declare conditionally constitutional and conditionally unconstitutional according to the characteristics of norms of the law reviewed. The analysis was limited to the Court decisions from 2003 to 2017. The research result indicates that distinguishing characteristics of norms reviewed have no correlation with conditionally constitutional or conditionally unconstitutional options.  Conditionally Constitutional Decision was used by the Court before replaced by Conditionally Unconstitutional Decision due to the weakness of decision implementation. For conditionally unconstitutional decisions are connected to the substance of the decision, creating a new norm that replaces, limit, or elaborate reviewed norm. The conditional decision is still required due to the following three aspects: enforcement of the supremacy of the constitution, the presumption of validity, and strengthening the execution of Constitutional Court decisions.